The Concept of Islamic Family Education (Study on Tafsir Ali-Imran Verses 33-37) and Its Implementation in Millennial Families - Fatkhu Syahril Mubarok; Imam Fauji (Universitas Muhammadiyah Sidoarjo, 2022)
, The purpose of this study is to find out how the concept of Islamic family education is contained in the letter Ali-Imran verses 33-37. In this case the researcher provides answers to the following questions: 1. How is the concept of Islamic family education in accordance with the Tafsir of Ali' Imran verses 33-37. 2. How is the implementation of millennial family education in Taman Anggun Sejahtera Housing 3 Kepuh Kemiri Village. This type of research uses qualitative research for the method used in this study, namely using the analytical method or analysis. The approach used in this research is to use a descriptive approach, which is to explain the meanings contained in each verse from the main source, namely the interpretation of Surah Ali-Imran verses 33-37 and analyze the meaning contained in secondary data sources so that the results are obtained in order to answer the questions at hand. The results of the research findings show that: (1) in the concept of Islamic family education contained in the letter Ali-Imran verses 33-37 the results of the traveler's analysis are faith education, worship education, da'wah education and moral education. (2) the application of Islamic family education in the letter Ali-Imran verses 33-37 with current education, namely by instilling values that are applied every day both in the family and in the community so that the hope is able to be used as the foundation of a strong Islamic family in a person's family. Muslim.